Pengaruh perbandingan sosial terhadap ketidakpuasan tubuh pada remaja akhir perempuan (studi tentang physical appearance) - Ridha Tantriloka Prameswari (Fakultas Psikologi, 2020)
Beauty standard that apply in the society make teenager feel dissatifaction about the body shape. Late adolescene doing social comparison for evaluation appearance purpose. The purpose of this research was determine the influence of social comparison on body dissatisfaction. This research is a quantitative nonexperimental regression form. The subject of this research amounted to 155 late adolescene females with age range of 18 – 21 years, weight minimal 50 kg and height maximal 160 cm. The scale of social comparison is Physical Appearance Comparison Scale – Revisied (PACS–R) will be developed by reasearchers and scale of body dissatisfaction is Multidimensional Body Self Relation Questionnaire-Appearance Scale (MBSRQ-AS) will be developed by researchers. The results of a simple regression analyse is the coefficient of determination (r2 ) 0.315 and sig (p) 0,000. (p < 0,05). Tthe correlation coefficient (r) 0,561 which means there is an influence of social comparison and body dissatisfaction 31,5 %